Evaluability assessment of Thriving Places : a report for Glasgow Community Planning Partnership /: a report for Glasgow Community Planning Partnership. (February 2017) - Brunner, Richard, 1965-; (Senior research fellow), Craig, Peter; Watson, Nick, 1960-
No abstract available